Perlindungan Hukum Terhadap Data Pasien Telemedicine Dalam Menerima Pelayanan Medis Berbasis Online - Annisa Arfah, Najmah; Puspitosari, Hervina (CV RIFAINSTITUT, 2023)
The implementation of telemedicine healthcare services utilizes electronic systems that are susceptible to hacking and illegal access by unauthorized parties. Article 15 of Information and Electronic Transactions Law, which is responsible for data security in electronic system providers, still lacks clear norms that require legal certainty in telemedicine implementation. In practice, data breaches are frequently found in electronic system providers. This has the potential to create legal risks that may result in the violation of patient data confidentiality and medical records through telemedicine applications. This research aims to identify and analyze the legal protection for patient data in telemedicine, as well as the efforts and criminal liability of healthcare service facilities regarding patients' personal data during online medical services. The research adopts a normative juridical approach with a statute approach to legal provisions. The data analysis method used in this research is qualitative normative analysis of primary and secondary data. The findings of this research highlight the legal protection for patient data in telemedicine, as stipulated in the Republic of Indonesia Law Number 27 of 2022 concerning Personal Data Protection, along with policies implemented by healthcare service facilities as controllers of personal data. The legal protection for telemedicine patient data includes personal data and medical records, while the accountability of healthcare service facilities entails administrative sanctions and imprisonment in accordance with the Personal Data Protection Law if unlawful acts that harm patients, such as data breaches or the release of false data. Patient data, including personal information and medical records, are crucial and confidential, thus requiring protection.